Subsídos agrícolas da China: Desafios entre a demanda doméstica e os compromissos com a Organizaç\~ao Mundial do Comércio (OMC) - Scarlett Queen Almeida Bispo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Chinese society has transformed in recent decades, moving from a predominantly agricultural country to one of the largest economies in the world. However, the accelerated industrialization and urbanization process has created considerable gaps between the rural and urban areas and the opportunity cost of continuing in the countryside has become very high, making it necessary to intervene through subsidy policies that stimulate agricultural production, mainly grains, which were adopted in different ways until the end of the 90s. When China joined the World Trade Organization in 2001, its domestic support had to be within the limits set for all member countries. So, it is important to know how the Asian country faced the growing domestic demand for food and at the same time, how did regulated subsidies according to WTO rules. To this end, data from 2011 to 2016 on Notifications from China were analyzed, which revealed some difficulty in staying within the limits as well as opening up short-term opportunities for several grain supply countries, including Brazil, to increase their exports to China.
Keywords: H71; Q17; Q18; Q11; 330; China; domestic support; agricultural policy; subsidies